The Effect of Leader-Member Exchange On Job Craftıng In Nursıng: The medıatıng role of psychologıcal safety - Eren Akman; Emre ISCI (ACHSM, 2023)
Background: Nurses are expected to make prompt and accurate decisions, have high crisis management skills, and exhibit proactive behaviors due to the nature of their service. Nevertheless, this situation is thought to be affected by the directors' approach and the working environment's structure. Therefore, this study aims to determine the mediating role of psychological safety in the effect of leader-member exchange on job crafting. Methods: This study is a descriptive cross-sectional study. The study was conducted with 782 nurses in Istanbul, Turkey. Structural equation modeling was used in the study. AMOS software was used for model analysis, and SPSS software was used for descriptive statistics and correlation analysis. Results: The results indicate that the effects of leader-member exchange on job crafting (β = .541, p < .05) and psychological safety (β = .430, p < .05) are statistically significant. Moreover, the effect of psychological safety on job crafting is statistically significant (β = .453, p < .05). Based on the path analysis, it was determined that psychological safety has a mediating role in the relationship between leader-member exchange and job crafting (Confidence Interval; LB=0.059, UB=0.172). Conclusion: This study revealed that psychological safety is a mechanism that contributes to the explanation of the relationship between leader-member exchange and job crafting. The findings will create ideas for directors to provide a healthier working environment. This situation is predicted to bring more positive results for employees and patients.